2014
DOI: 10.3340/jkns.2014.56.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Delirium after Spine Surgery in Elderly Patients

Abstract: ObjectivePostoperative delirium is a common complication in the elderly after surgery but few papers have reported after spinal surgery. We analyzed various risk factors for postoperative delirium after spine surgery.MethodsBetween May 2012 and September 2013, 70 patients over 60 years of age were examined. The patients were divided into two groups : Group A with delirium and Group B without delirium. Cognitive function was examined with the Mini-Mental State Examination-Korea (MMSE-K), Clinical Dementia Ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 34 publications
(63 reference statements)
2
34
1
Order By: Relevance
“…Several studies have reported that postoperative delirium increases hospitalization, in-hospital cost, and mortality, and the reported risk factors include advanced age and a personal history of alcohol/drug abuse, depression, psychotic disorders, neurological disorders, anemia, fluid/electrolyte disorders, and weight loss. Moreover, postoperative delirium occurs more frequently in the PreCI group, and their duration of stay is longer 2 3 12) . Therefore, interventions that increase the early detection of delirium have the potential to decrease the severity and duration of delirium and prevent unnecessary suffering and costs from the complications of delirium and unnecessary readmissions to the hospital 2) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported that postoperative delirium increases hospitalization, in-hospital cost, and mortality, and the reported risk factors include advanced age and a personal history of alcohol/drug abuse, depression, psychotic disorders, neurological disorders, anemia, fluid/electrolyte disorders, and weight loss. Moreover, postoperative delirium occurs more frequently in the PreCI group, and their duration of stay is longer 2 3 12) . Therefore, interventions that increase the early detection of delirium have the potential to decrease the severity and duration of delirium and prevent unnecessary suffering and costs from the complications of delirium and unnecessary readmissions to the hospital 2) .…”
Section: Discussionmentioning
confidence: 99%
“…Inouye et al 6 7) have presented a multifactorial model for delirium, which showed a close association of postoperative delirium with predisposing factors (e.g., dementia and severe illness) and precipitating events (e.g., major surgery, anesthesia, and multiple psychoactive medications). The factor with the biggest impact on postoperative delirium in hip fracture and spine surgery has been reported to be preoperative dementia 8 12) . Although there have been reports about the precise assessment and incidence of preoperative dementia in cardiac surgery, few studies have been performed on the assessment and incidence of preoperative CI for spine surgery, in which subjective symptoms are very important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies performed preliminary evaluations of this relationship treating duration of surgery as categorical variable and secondary endpoint. They reported mean delirium incidences of 14% for durations of surgery less than 180 minutes, 33% for 180 to 300 minutes and 48% for surgeries lasting longer than 300 minutes (34)(35)(36)(37)(38). We extend on these previous findings by using a binary logistic regression model that provides the intriguing perspective to estimate how the odds of becoming delirious change with every minute of surgery.…”
Section: Sample Size Calculation and Statistical Methodsmentioning
confidence: 66%
“…Five prospective studies evaluated POD following spine surgery and unambiguously identified advanced age, lower preoperative cognitive level, general anesthesia and intraoperative hypotension as risk factors (34)(35)(36)(37)(38). The reported incidence of delirium yet varied substantially between 8% and 41%, which is not resolved by clear methodological differences since all studies included patients of similar age (mean age between 70 and 75 years) and used validated instruments for the diagnosis of delirium.…”
Section: Introductionmentioning
confidence: 99%